Implementing Process Mining in Indonesia Health Care: Challenges and Potentials - Guntur Prabawa Kusuma; Angelina Prima Kurniati; Firdaus Hafidz; Owen Ashby Johnson (IJAIT (International Journal of Applied Information Technology), 2023)
Indonesia has become one of the countries having the biggest single-payer national insurance with a population-based membership. The insurance had helped up to 217 million patients since its inception in 2014. Capturing insights from a large-scale electronic health record has the potential to give a valuable improvement to the health care processes quality. Process mining is an emerging approach to â€œbridgeâ€ between the domain of data science and process science. It has also been recognized to contribute to the domain of health care where complex and multi-discipline processes are happening. The BPJS Kesehatan data containing routinely collected medical records becomes a valuable source of knowledge to improve the quality of health care. In contrast to its benefits, exploiting and managing population-based health care data for research brings challenges and potential. This paper presents the challenges of conducting process mining projects in the perspective of diversity, data quality, ethics, and security. Process mining in health care also brings potentials in care process comparisons, precision medicine, audit and compliance, and the opportunities of using virtual research environment to conduct research using a population-based data set based on unique characteristics of human biology.